Sedimentation velocity analytical ultracentrifugation for characterization of therapeutic antibodies - Uchiyama, Susumu (Biophys Rev, 2017)
Sedimentation velocity analytical ultracentrifugation (SV-AUC) coupled with direct computational fitting of the observed concentration profiles (sedimentating boundary) have been developed and widely used for the characterization of macromolecules and nanoparticles in solution. In particular, size distribution analysis by SV-AUC has become a reliable and essential approach for the characterization of biopharmaceuticals including therapeutic antibodies. In this review, we describe the importance and advantages of SV-AUC for studying biopharmaceuticals, with an emphasis on strategies for sample preparation, data acquisition, and data analysis. Recent discoveries enabled by AUC with a fluorescence detection system and potential future applications are also discussed.